The Influence Of Village Funds On Development Disparity Between Districts In Bengkulu Province - Hutapia, Wazir; Almanuar, Benardin (Jurnal AGRISEP, 2020)
The problem of development disparity between districts and cities in Bengkulu Province, as indicated by the relatively high and fluctuating Gini Index figures, meanwhile village funds received by the district government always increase from year to year. Therefore this study aims to find out how much influence village funds have on development disparities between districts in Bengkulu province. This study uses secondary data, obtained from the Central Statistics Bureau and the Ministry of Finance. The research sample was all districts in Bengkulu Province, except Bengkulu City because they did not receive village fund, and analysis techniques using the Panel Data regression model. The appropriate model is Fixed Effect, but the regression coefficient is very small but it has a role in reducing development inequality (Gini Index). The small effect is because the village fund provided are still very small and the formulation of the distribution of village funds is not pro to the poor population. Many other factors affect development inequality such as: differences in endowment factors, demographic conditions, lack of smooth mobility of goods and services, concentration of regional economic activities, allocation of development funds between regions.